ENHANCING BUSINESS PERFORMANCE OF PT. BENTOEL PRIMA - Gabriel Bin Susabda; Ryan Eleazar (International Journal of Applied Business and International Management, 2018)
Currently, PT. Bentoel Internasional Investama, Tbk ("Bentoel" or "Company") and its subsidiaries, is a member of the British American Tobacco Group, the world's second largest tobacco group by global market share with trademarks in more than 200 countries. Bentoel is the fourth largest cigarette producer in Indonesia with a market share of 7%. Bentoel manufactures and markets a wide range of tobacco products such as machine clove cigarettes, hand-rolled cigarettes and white cigarettes. Our main portfolio includes Dunhill Filter, Dunhill Mild, Club Mild and Lucky Strike Mild. We also produce and market local brands such as Neo Mild, Tali Jagat, Bintang Buana, Sejati, Star Mild and Uno Mild, as well as global brands such as Lucky Strike and Dunhill. Bentoel employs over 6,000 employees, from starting to build partnerships with tobacco farmers, buying and processing leaf tobacco and cloves, to cigarette production, marketing and distribution.